Cardiometabolic risk in adolescents students of high school: influence of work - Pedro Henrique Urbano de Freitas; José Luiz Tatagiba Lamas; Ana Carolina Lopes Ottoni Gothardo; Tania Calixto Sofiato; Maíra Rezende Girardi; Cíntia Christina Bastos; Séfora Carneiro Bonillo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to evaluate and compare the prevalence of cardiometabolic risk factors among high school adolescents with or without jobs, and to establish an association between risk factors and changes in lifestyle after starting to work. Methods: quantitative cross-sectional study. An instrument was applied to assess socio-demographic characteristics and habits. Dietary pattern was assessed by the Brazilian Healthy Eating Index. Nutritional status was assessed by the Z-score. Data were submitted to statistical analysis and comparison between groups and periods, as well as association and correlation was done. Results: the prevalence of high blood pressure was 7.7%. High BP affected 4.5% of non-workers and 10.9% of workers. Dietary patterns were inappropriate and 51.2% did not engage in physical activity. The prevalence of obesity was 28.3%. The results showed an association between work and alcohol consumption, lack of physical activity and reduced sleep quality. Conclusions: work increased exposure to certain cardiometabolic risk factors.